Analysis of Mark UP value decisions with a bidding strategy model to win projects in government auctions - Nyoman Rowin Sinaya; Parwadi Moengin; Bambang Endro Yuwono; Darmawan Pontan (Publikasi Indonesia, 2024)
The purpose of this study is to create a bidding strategy to determine the optimum markup value and maximum expected profit to win a project auction. From the data selection results, 24 project tenders and 12 large qualification companies participated in the tender on the LPSE page of the Ministry of PUPR, which will be used as samples in this study. The bid strategy model used to calculate the optimum markup value and maximum expected profit are with 3 (three) bid strategy models, namely the Friedman Model, Gates Model and Ackoff & Sasieni Model, and to calculate the probability of winning using the statistical approach method of multi discrete distribution, normal multi-distribution and single normal distribution. From the results of testing models with optimal mark-ups for the 24 project tenders used in this study, the percentage for each bidding strategy model that has the potential to win the tender sequentially is the Friedman model by 80.56%, the Gates model by 61.11% and the Ackoff &; Sasieni model by 43.06%. So, it can be concluded that the Friedman model provides a fairly high chance of winning tenders in government projects within the Ministry of PUPR.